Influence of Semiconductor Thickness and Molecular Weight on the Charge Transport of a Naphthalenediimide-Based Copolymer in Thin-Film Transistors - Karpov, Yevhen; Zhao, Wei; Raguzin, Ivan; Beryozkina, Tetyana; Bakulev, Vasiliy; Al-Hussein, Mahmoud; Haeussler, Liane; Stamm, Manfred; Voit, Brigitte; Facchetti, Antonio; Tkachov, Roman; Kiriy, Anton (ACS Applied Materials and Interfaces, 2015)
The N-type semiconducting polymer, P(NDI2OD-T2), with different molecular weights (MW = 23, 72, and 250 kg/mol) was used for the fabrication of field-effect transistors (FETs) with different semiconductor layer thicknesses. FETs with semiconductor layer thicknesses from ∼15 to 50 nm exhibit similar electron mobilities (μ's) of 0.2-0.45 cm2 V-1 s-1. Reduction of the active film thickness led to decreased values; however, FETs with ∼2 and ∼5 nm thick P(NDI2OD-T2) films still exhibit substantial μs of 0.01-0.02 and ∼10-4 cm2 V-1 s-1, respectively. Interestingly, the lowest molecular weight sample (P-23, MW ≈ 23 kg/mol, polydispersity index (PDI) = 1.9) exhibited higher the highest molecular weight sample (P-250, MW ≈ 250 kg/mol, PDI = 2.3) measured for thicker devices (15-50 nm). This is rather unusual behavior because typically charge carrier mobility increases with MW where improved grain-to-grain connectivity usually enhances transport events. We attribute this result to the high crystallinity of the lowest MW sample, as confirmed by differential scanning calorimetry and X-ray diffraction studies, which may (over)compensate for other effects.
CRIS-Team Scopus Importer:2023-03-20
Keywords: crystallinity; electron mobility; morphology; semiconducting polymer; thin-film transistor